Zn2(Y)·H2O, (Me4N)2H2Y·3ZnCl2, (Me4N)4Y·5ZnCl2·H2O, (BzNMe3)2H2Y·2ZnBr2, Zn(H2Y)·4ZnCl2·2EtOH·14H2O AND Zn(H2Y)·6ZnCl2·2EtOH·6H2O (Y = EDTA): SYNTHESIS AND INFRARED STUDY - SERIGNE CISSE; IBRAHIMA CISSE; LIBASSE DIOP (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
Six acidic or neutral ethylenediaminetetraacetato [H2Y2-, H3Y- or Y4-] containing adducts and derivatives have been synthesized and studied by infrared. The suggested structures are discrete with octahedral or tetrahedral environments around the zinc centres, the ethylenediaminetetraacetic anion behaving as a bichelating, trichelating, tetrachelating and hydrogen bonds involved, pentachelating or hexachelating and hydrogen bonds involved ligand. For most of the structures when intermolecular hydrogen bonds are considered, a supramolecular architecture is obtained.